Business Models in Accounting Research in the Light of Innovation Diffusion Theories - Kozarkiewicz , Alina (Studia Oeconomica Posnaniensia, 2016)
The aim of this paper is to discuss the processes and mechanisms influencing the phenomenon of the increasing interests in the business model concept among accounting researchers. The foundations for the analysis are the theories of innovation diffusion. In the first part of the paper, the most important theories representing key orientations: rational (economic) and sociological (based on social mechanism) are discussed briefly. In the next part of the paper, on the basis of bibliometric research conducted on selected publication collections, the scope and the pace of the diffusion of the business model concept in accounting journals are demonstrated. As the research implies, it is an early stage of diffusion process; however, some new trends in the interests of accounting researchers are to be recognized.